2020
DOI: 10.1017/s0263574720000247
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Planning of Quadrotor Systems for Various Objective Functions

Abstract: SUMMARY Quadrotors are unmanned aerial vehicles with many potential applications ranging from mapping to supporting rescue operations. A key feature required for the use of these vehicles under complex conditions is a technique to analytically solve the problem of trajectory planning. Hence, this paper presents a heuristic approach for optimal path planning that the optimization strategy is based on the indirect solution of the open-loop optimal control problem. Firstly, an adequate dynamic system modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…An extensive review article on motion planning of quadcopters or drones and their various control techniques was reported by Elijah et al [8] , and although these authors discussed the physical results associated with the experimental deployment of a quadcopter, they were not elaborately reported in that work. Moreover, Heidari and Saska [9] briefly discussed the different types of quadcopters such as fixed-wing and multi-rotor and their advantages and disadvantages in various applications with a comparative analysis. The research by Abdalla and Al-Baradie [10] integrated the PSO algorithm with the PID controller to design a steer control scheme for a quadcopter.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive review article on motion planning of quadcopters or drones and their various control techniques was reported by Elijah et al [8] , and although these authors discussed the physical results associated with the experimental deployment of a quadcopter, they were not elaborately reported in that work. Moreover, Heidari and Saska [9] briefly discussed the different types of quadcopters such as fixed-wing and multi-rotor and their advantages and disadvantages in various applications with a comparative analysis. The research by Abdalla and Al-Baradie [10] integrated the PSO algorithm with the PID controller to design a steer control scheme for a quadcopter.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…However, Besada-Portas et al [18]; Cui and Wang [19]; and Yao and Zhao [20] have shown the software-based computer simulation results of UAVs in their studies. Heidari and Saska [9] developed a heuristic approach-based open-loop control system to select optimal values of the dynamic control parameters such as thrust force and torque of a quadcopter for trajectory optimisation.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…There are a few kinds of research in this area that represents a complete solution for autonomous landing problem and takes into the account the real-world challenges [25,26]. In general, optimal path generation should make the autonomous landing maneuver faster [27]. But, in our opinion, development of a fast and robust motion controller for quadrotor system can make critical improvements on landing time and precision in the real-world experiments that wind-induced disturbance forces are unavoidable.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, various studies conducted and number of methods have been proposed. Detailed articles survey were accomplished to define the current state of the art of path planning problem in literature [11][12][13]. For motion planning and autonomy subjects, numerous researches exist in different manuscripts and number of methods are being presented.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is implemented in a lightweight quadrotor platform and is evaluated in unknown cluttered indoor and outdoor workspaces. In, The optimal path planning algorithm was proposed by Heidari and Saska [23] for a quadrotor by considering various objective functions, such as energy efficiency. The necessary conditions of optimality are formulated here as a normal form of a two-point boundary-value problem using Pontryagin's minimum principle.…”
Section: Introductionmentioning
confidence: 99%